PERPUSTAKAAN ANAK DENGAN PENDEKATAN PSIKOLOGI ARSITEKTUR DI SURAKARTA - Iyud Ditta Oktara; M.D.E Purnomo; Ana Hardiana (ARSITEKTURA, 2015)
The existance of children library in Surakarta could become a supporting facility for formal education which can increase children interest in reading, and support Surakarta Goverment efforts on increasing public interest in reading since early cildhood.  The purpose of this planning is to obtain a design of children library as a means to improve Surakarta children’s interest in reading by using architectural psychology as a design approach. The issue that arises is how to apply the principles of architectural psychology in the children library design. In this planning, studies are done to determine principles of psychological architecture for children library in Surakarta which give the best influence, psychologically, towards children as the main users of this building.The result obtained is a design of children library that adapts the characteristics of children by applying the principles of architectural psychology in building’s interior and exterior, creating a children library with interesting, fun, and comfortable atmosphere. Keywords: Children Library, Architectural Psychology